The occurrence of the Monarch butterfly, Danaus plexippus L. in the Azores, with a brief review of its biology. - Neves, Verónica C. (2001)
The Monarch butterfly, Danaus plexippus L. (Lepidoptera, Nymphalidae), has been an occasional visitor to the Azores. However, during the last two decades it has become a resident species in these islands and has adapted its behaviour to the geographic conditions of this new habitat, feeding on Gomphocarpus fruticosus (L.) Aiton fil. (Asclepiadaceae). The first confirmed breeding of this butterfly in the Azores (Faial island) is reported here and dates from the summer of 1994. However, previous sightings of only a very few adult individuals indicate that there was already a small resident population before 1994. Breeding was confirmed in three additional sites: on 3 June 1999, three adults of Monarch butterfly were observed laying eggs on G. fruticosus bushes near Ribeirinha and on 28 June 1999, several caterpillars were found in the same place. Larvae were also found at S. Roque (Pico island) and larvae and pupae at S. Carlos (Terceira island) in the summer of 1999. Monarch butterflies have been observed, occasionally, in Faial, Pico, Terceira, São Miguel, Santa Maria and Corvo during winter and spring, indicating the existence of a resident population all year round, but the vegetation used for wintering shelters has not yet been confirmed.